2011
DOI: 10.1152/ajpgi.00496.2010
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the understanding of mineral and bone metabolism in inflammatory bowel diseases

Abstract: Ghishan FK, Kiela PR. Advances in the understanding of mineral and bone metabolism in inflammatory bowel diseases. Am J Physiol Gastrointest Liver Physiol 300: G191-G201, 2011. First published November 18, 2010 doi:10.1152/ajpgi.00496.2010.-Chronic inflammatory disorders such as inflammatory bowel diseases (IBDs) affect bone metabolism and are frequently associated with the presence of osteopenia, osteoporosis, and increased risk of fractures. Although several mechanisms may contribute to skeletal abnormaliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 109 publications
4
76
0
1
Order By: Relevance
“…The effects of vitamin D alone or in combination with bisphosphonates in BMD in IBD patients yielded inconclusive data, with some studies indicating significant benefits (46), limited effects (5), or no effect (6). In light of the increasing complexity of the gut-renal-skeletal axis and the associated regulatory networks, we have postulated that supplementation with a high dose of vitamin D 3 may be detrimental or have a limited beneficial potential to bone health if used during the uncontrolled phase of inflammation in IBD patients, and we have suggested that, in patients at clear risk of osteopenia or osteoporosis or with proven osteopenia or osteoporosis, vitamin D 3 be withheld until remission is achieved (18,19). To test this hypothesis, we used an established and clinically relevant model of adoptive T cell transfer colitis induced under dietary supply of HED of ϳ730 IU/day.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of vitamin D alone or in combination with bisphosphonates in BMD in IBD patients yielded inconclusive data, with some studies indicating significant benefits (46), limited effects (5), or no effect (6). In light of the increasing complexity of the gut-renal-skeletal axis and the associated regulatory networks, we have postulated that supplementation with a high dose of vitamin D 3 may be detrimental or have a limited beneficial potential to bone health if used during the uncontrolled phase of inflammation in IBD patients, and we have suggested that, in patients at clear risk of osteopenia or osteoporosis or with proven osteopenia or osteoporosis, vitamin D 3 be withheld until remission is achieved (18,19). To test this hypothesis, we used an established and clinically relevant model of adoptive T cell transfer colitis induced under dietary supply of HED of ϳ730 IU/day.…”
Section: Discussionmentioning
confidence: 99%
“…(43). On the patient level, the results from different studies do not specifically implicate dairy products (82), although low calcium and low vitamin D are risks for osteopenia (83,84), and associated with increased risk for colorectal cancer (85). There are fewer cohort studies examining the impact of dairy food consumption on IBD.…”
Section: Effect Of Milk and Dairy Foods On Diseasementioning
confidence: 99%
“…Systemic imbalance of Ca 2ϩ homeostasis, including disturbed renal and intestinal Ca 2ϩ (re)absorption, has been hypothesized to contribute to the pathophysiology of bone loss associated with chronic inflammatory disorders, and especially with inflammatory bowel diseases (IBD) 3 (3,4). Indeed, increased urinary Ca 2ϩ excretion has been described in IBD patients and in mouse models of colitis (5,6).…”
Section: Ncx1 Is a Namentioning
confidence: 99%